THE POTENCY OF PROTEIN EXTRACTS FROMCandida albicans AS BIORECEPTOR ON IMMUNOSENSOR FOR DIAGNOSIS OF CANDIDIASIS - Masfufatun -; Noer Kumala; Afaf Baktir (PROSIDING SEMINAR KIMIA, 2015)
Currently diagnosis of candidiasis still usingthe traditional standard blood culture method. The traditional method were less sensitive andtime consuming. The purpose of this research were to develope the more sensitive immunosensor based method, and to examine the potency of C. albicans protein extract as bioreceptor to detect C. albicans and its biofilm in the blood of candidiasis patients.The research methods include: (1) preparation of digestive gland liquid of snail (Achatina fulica); (2) extraction of protein from C. albicans through enzimatis and mechanic methods and (3) analyzing the protein extract as bioreseptor through immunodot assay.The research results showed that the snail enzymes has protein content 1.35 mg/ml and specific activity 1.96 unit/mg. The snail enzyme hydrolyzed the cell wall of C. albicans with and without sonication, produced planktonic extracell protein extract (PEP) and biofilm extracell proteinextract (BEP), planktonic intracell protein extract (PIP), and biofilm intracell protein extract (BIP), with protein content 1.44; 1.29; 1.29 and 1.21 mg/ml respectively. The biofilm intracell protein (BIP) showed antigenic property toward antibody anti-Candida (positive control),giving red spot on imunodot assay. Immunodot assay can distinguish negative control serum (health man) and positive Candidiasis control by using antigen 1 g/l and 50 l serum.